ANALYSIS OF THE EFFECTIVENESS OF SOCIAL MEDIA MARKETING ON CONSUMER BEHAVIOR IN THE MILLENNIAL GENERATION - Mulia Sosiady; Ermansyah (Adisam Publisher, 2025)
This research aims to analyze the effectiveness of social media marketing on consumer behavior in the millennial generation through a comprehensive literature review. Millennials, known as digital natives, show a strong preference for social media platforms as primary channels for interaction and information consumption. This research examines various published empirical studies to identify key factors that influence the effectiveness of social media marketing, including content type, interaction methods, and use of analytical data. The results of the literature review show that interactive, authentic and relevant content plays an important role in increasing engagement and loyalty of millennial consumers. In addition, collaboration with influencers, especially micro-influencers, is an effective strategy in building trust and expanding marketing reach. The use of innovative features such as short videos, live streaming and augmented reality has proven to be able to maintain attention and increase consumer interest. Research also finds that brand awareness and commitment to issues of sustainability and social responsibility have a significant impact on millennial consumer preferences and loyalty. Brands that actively support social and environmental campaigns are able to build a positive image and strengthen long-term relationships with consumers. This review concludes that effective social media marketing must combine creative content strategies, intelligent use of data, authentic interactions, and a commitment to social responsibility to achieve maximum impact on millennial consumer behavior. The study recommends further research to explore specific dynamics across different social media platforms and different industries.